POST COVID-19 PANDEMIC: COMPARATIVE STUDY IN THE VALUE RELEVANCE OF ACCOUNTING INFORMATION BETWEEN LISTED MANUFACTURING FIRMS AND LISTED SERVICE FIRMS IN NIGERIA - Abubakar Aliyu; Abbas, Abdulrahman Ngadi; Abdu, Abubakar (Gusau Journal of Accounting and Finance)
The study investigated the differences in the value relevance of accounting information between the listed service firms and the listed manufacturing firms in Nigeria in the post COVID-19 period. Secondary data was used from the annual reports of the sampled firms and cash craft stock broker website between 2021 and 2023. correlation research design was used. The population of the study included all the seventy-three listed manufacturing firms and twenty three listed service firms in Nigeria as at 31st December, 2023. The sample size was fifty-two firms from the listed manufacturing firms and twenty from the listed service firms; multiple panel regression model was used for the purpose of analysis. Based on the findings of the study, earnings per share and book value of equity reported by listed manufacturing firms determines share price more than the ones reported by the listed service firms. However, divided among the listed service firms should be given preference over dividend reported by the listed manufacturing firms in Nigeria in equity valuation. Additionally, listed manufacturing and financial service firms in Nigeria should work towards increasing their earnings as it determines share price. As well, they should suitably manage their book value, pay dividend to investors from the profit generated and a balance should be strike between cash inflow and out flow from operations to avoid cash shortage or keeping unneeded cash. Moreover, SEC and FRC should maintain their effort in ensuring the integrity of information released by the listed firms in Nigeria.